Inverse Synthetic Aperture Radar Imaging with MATLAB Algorithms - With Advanced SAR/ISAR Imaging Concepts, Algorithms, and MATLAB Codes (2nd Edition) - Özdemir Caner (John Wiley & Sons, 2021)
The newly revised Second Edition of this book covers in greater detail the fundamental and advanced topics necessary for a complete understanding of inverse synthetic aperture radar (ISAR) imaging and its concepts. Distinguished author and academician, describes the practical aspects of ISAR imaging and presents illustrative examples of the radar signal processing algorithms used for ISAR imaging. The topics in each chapter are supplemented with MATLAB codes to assist readers in better understanding each of the principles discussed within the book. This new edition includes discussions of the most up-to-date topics to arise in the field of ISAR imaging and ISAR hardware design. The book provides a comprehensive analysis of advanced techniques like Fourier-based radar imaging algorithms, and motion compensation techniques along with radar fundamentals for readers new to the subject.